(untitled) (International Journal of Natural Sciences, 2016)
The present study was carried out to know the present status including general information, feeding, breeding, housing, milking etc. and costs and returns of small dairy farms, to compare the productive and reproductive performance of crossbred and indigenous cows and to make recommendation for development of small scales dairy farming. With this view, the empirical data were collected by using pretested questionnaire. The study was conducted at preselected 30 dairy farms in Chittagong suburban area, and four months-long survey was diminished on thirty small dairy owners. It appeared that 57% farm owners belong to business class and remaining 43% to different categories. Fifty three percent took dairying as a side-business whereas only 47% took it as a main business enterprise. Major percentage of farm owner education level was Higher Secondary (60%). The dry period, calving interval, services per conception and days open of crossbred was 98.5±18.9, 419±11,3.1±0.82, 118±25.8 and indigenous was 140±10.4, 428±24.7,1.95±0.44, 137±7.78 respectively. The study showed that there were significant (P<0.01) differences within the dry period, services per conception, calving to first service, highest and lowest milk production and lactation period of crossbred and indigenous dairy cows. The study also showed non-significant differences within calving interval for crossbred and indigenous. In case of small dairy farming, the farms were facing a lot of problems such as scarcity of feeds and fodder, high price of concentrate and lack of technical knowledge. This type of dairy farming will be a potential sector for economic development of Bangladesh. International Journal of Natural Sciences (2015), 5(2) 59-65